Experimental and theoretical investigation of octahedral and square-planar isothiocyanato complexes of Ni(II) with acylhydrazones of 2-(diphenylphosphino)benzaldehyde. (29th March 2015) - Čobeljić, Božidar; Pevec, Andrej; Stepanović, Stepan; Spasojević, Vojislav; Milenković, Milica; Turel, Iztok; Swart, Marcel; Gruden-Pavlović, Maja; Adaila, Kawther; Anđelković, Katarina
Graphical abstract: Synthesis and characterization of octahedral and square-planar isothiocyanato Ni(II) complexes with acylhydrazones of 2-(diphenylphosphino)benzaldehyde. DFT explanation of the influence of phosphine ligand protonation on geometry and stoichiometry of complexes. Magnetic properties of octahedral Ni(II) complex. Abstract: Octahedral and square-planar isothiocyanato complexes of Ni(II) with the condensation derivative of 2-(diphenylphosphino)benzaldehyde and Girard's T reagent were synthesized and characterized by elemental analysis, IR spectroscopy and X-ray crystallography. Results of magnetic measurements for octahedral Ni(II) complex were also reported. In all the complexes the ligand is coordinated as tridentate via the phosphorus, the imine nitrogen and the carbonyl oxygen atoms while the remaining coordination positions are occupied with thiocyanato anions. Coordination of deprotonated phosphine ligand results in formation of square-planar complexes, while the octahedral complex was formed with protonated ligand. Reaction energetics with both forms of ligand were studied by the means of DFT and results were in complete agreement with experimental observations. Furthermore, ligand field splitting analysis gave the deeper insight in the relationship of the isolated complex coordination environment and protonation of the ligand.